2012
DOI: 10.1111/and.12058
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mRNA aromatase in ejaculated spermatozoa from infertile men in relation to either asthenozoospermia or teratozoospermia

Abstract: Oestrogen biosynthesis in ejaculated spermatozoa is an autonomous process, which may influence sperm functions. The purpose of this study was to evaluate the relationship between the expression of aromatase, sperm quality and seminal neutral α-glucosidase marker in semen of Tunisian infertile men: asthenozoospermia (A; n = 16), teratozoospermia (T; n = 12) and asthenoteratozoospermia (AT; n = 11) in comparison with 18 normozoospermic ones. Aromatase mRNA levels estimated by real-time PCR were reduced in groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
(62 reference statements)
3
4
0
1
Order By: Relevance
“…Moreover, the levels of NAG in patients with teratozoospermia and oligoasthenospermia were significantly higher than those in patients with severe oligozoospermia. These data confirmed that NAG was significantly associated with semen concentration, motility and morphology, which was consistent with current studies (Levrant et al., ; Pena et al., ; Said, Saad, & Carreau, ; Said, Saad, Luna et al., ), but was not in line with the study reported by Pena, et al. ().…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the levels of NAG in patients with teratozoospermia and oligoasthenospermia were significantly higher than those in patients with severe oligozoospermia. These data confirmed that NAG was significantly associated with semen concentration, motility and morphology, which was consistent with current studies (Levrant et al., ; Pena et al., ; Said, Saad, & Carreau, ; Said, Saad, Luna et al., ), but was not in line with the study reported by Pena, et al. ().…”
Section: Resultssupporting
confidence: 90%
“…Sperm dysfunction is frequently observed in most infertile men (Chemes & Rawe, ; Chua et al., ). According to the criteria of World Health Organization (WHO ), infertile patients were classified into normozoospermia, asthenozoospermia and teratozoospermia groups (Said, Saad, & Carreau, ; Said, Saad, Luna et al., ). Epididymis is an important place for sperm capacitation before fertilisation, which plays a key role in sperm maturation and motility (Moore, ; Pena, Sanchez, Vasquez, Castillo, & Miska, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, treatment with an estrogen receptor‐alpha agonist downregulates genes involved in spermiogenesis, 58 indicating that the changes in sperm motility observed in VFG35 may be related to the impact of venlafaxine‐induced high estrogen levels on tail formation during spermiogenesis. The strong inverse correlation between aromatase mRNA levels and the percentage of normal spermatozoa in humans 59 reinforces this idea and agrees with the increased number of spermatozoa with normal morphology in VFG65 as estrogen levels decreased. It is known that apoptosis during spermatogenesis enables the elimination of defective germ cells, 57 preventing the formation of abnormal spermatozoa.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, Carreau and co-workers reported that, in human ejaculated SPZ, the immotile sperm fraction showed low levels of P450arom, both mRNA and protein activity (30 and 50%, respectively), as compared with the motile sperm fraction (153155). In addition, the same authors have recently reported that in SPZ from asthenospermic, teratospermic, and asthenoteratospermic patients, P450arom mRNA levels were progressively lower as compared with SPZ from control patients (156). The hypothesis that E 2 treatment improves motility by enhancing oxidative metabolism and the intracellular ATP concentrations in human sperm (157, 158) well fit with the observation that E 2 can regulate mitochondrial function in MCF7 cells by increasing nuclear respiratory factor-1 expression (159).…”
Section: Estrogens and Sperm Qualitymentioning
confidence: 89%